2015
DOI: 10.1111/jgh.13167
|View full text |Cite
|
Sign up to set email alerts
|

Risk of developing advanced colorectal neoplasia after removing high‐risk adenoma detected at index colonoscopy in young patients: A KASID study

Abstract: The cumulative incidence of overall and advanced colorectal neoplasms was significantly higher in older patients than in young patient groups. Age was a significant risk factor for developing colorectal neoplasms after removing high-risk adenoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 39 publications
1
28
0
Order By: Relevance
“…Our study included patients who were free of both low-risk and high-risk adenomas at baseline colonoscopy and showed that old age was strongly associated with the development of overall and high-risk adenomas. These results are consistent with those of large-scale stud- ies [6,8,9] that focused on advanced adenoma. To the best of our knowledge, this is the first report indicating that old age is a significant risk factor for high-risk adenomas at surveillance colonoscopy.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our study included patients who were free of both low-risk and high-risk adenomas at baseline colonoscopy and showed that old age was strongly associated with the development of overall and high-risk adenomas. These results are consistent with those of large-scale stud- ies [6,8,9] that focused on advanced adenoma. To the best of our knowledge, this is the first report indicating that old age is a significant risk factor for high-risk adenomas at surveillance colonoscopy.…”
Section: Discussionsupporting
confidence: 81%
“…However, the association between age and recurrent adenoma has differed from study to study. Recent several large-scale studies have reported that age is a significant predictor of advanced adenoma [6,8,9]; a pooled analysis reported that patient age had the strongest association with the risk of metachronous advanced adenoma [6]. Park et al [8] also demonstrated that the recurrence of overall and advanced adenoma was related to old age.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…When the outcome measure was detection of AN, at surveillance, the findings were similar, with five studies rated as low to moderate risk of bias12 98–101 identified. Four of the five studies reported significant associations, showing increased risk for AN at first surveillance if tubulovillous or villous components (rather than tubular) were identified at index.…”
Section: Resultsmentioning
confidence: 69%
“…Five studies12 98–101 only reported statistical analyses on AN, with four reporting no significant association between HGD at index and risk of AN at first surveillance, and the fifth study (Cubiella et al 100) reporting an OR of 0.7 (95% CI 0.5 to 0.98), consistent with reduced risk associated with HGD. Again, risk of bias was generally rated as moderate to low.…”
Section: Resultsmentioning
confidence: 98%